(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2022)
This study was premised to explore the causes of plagiarism and its extenuating circumstances in Higher Educational Institutions in Ghana. The study focused on Tertiary Students in the Kumasi and Sunyani Metropolis and Municipality respectively, 200 students were selected deploying a cluster sampling technique. The underpinning research paradigm was a cross sectional descriptive survey. Questionnaires were the main instrument used in eliciting primary data for the study. Secondary data were obtained from academic journals databases including EBSCO, and Google Scholar. The analyses were presented using Means, Standard Deviations, Unweighted Means, Relative Important Index (RII), Frequencies and Percentages. The study discovered the causes of student’s plagiarism as follows; poor writing skills, to obtain better marks poor understanding of plagiarism, cost of quality education materials with, Pressure from family and friends to offer help. The plagiarism extenuating factors were also discovered as follows; educate students on writing methods, assign different questions to different individuals, give tests quizzes or assignments more, assigning more in-class activities, not allowing students make up tests, rotate curriculum and trust building. It is recommended that deploying plagiarism detective software under covert study will help understand the causal factors better in order to inoculate students plagiarism.